Shear Test on Reinforced Clay - Chegenizadeh, Amin; Nikraz, Hamid (Trans Tech Publications Inc, 2011)
Composite soils have been widely used in civil engineering applications, especially in slopes, embankment dam and landfills. This paper aims to investigate effect of fiber inclusion on shear stress of composite soil (i.e. clay composite). A series of laboratory direct shear tests carried out to evaluate fiber effect on strength behavior of composite clay. Clay was selected as soil part of the composite and plastic fiber was used as reinforcement. The fiber parameters differed from one test to another, as fiber length were changed from 20 mm to 65 mm and fiber content were varied from 0.7% and 2%.Normal stress kept constant at 150 kpa. For each test, stress_ displacement graph derived and the results were compared. The results proved that inclusion of fiber affected shear stress behaviour of clay composite so that increasing in fiber content and length caused increasing in shear stress.